MODEL PENGENDALIAN KEMISKINAN DENGAN PENDEKATAN DIVERSIFIKASI USAHA, SUSTAINABLE DEVELOPMENT GOALDS (SDGS) DAN ECONOMIC VALUE (STUDI PADA DAERAH PEMEKARAN DI SUMATERA UTARA) - Muhammad Toyib Daulay (Universitas Negeri Medan, 2017)
This research has the goal of providing input to economic divesifikasi models which are the most consistent in increasing economic value and decrease poverty in the district town expansion North Sumatra Province. Provide input model Sustaianble Development Goals (SDGs) are the most supportive in the increase in economic value and alleviating poverty in the county town expansion North Sumatra Province. Prove empirically the performance of the economy which interact strongly supported the decline in poverty in the county townof the expansion in North Sumatra Province. This research uses 16 sample extraction area in North Sumatra. The first model of poverty alleviation through diversified value-added business community in meeting the needs of the community's life while the second model to determine what variables as policy recommendations for alleviating poverty in the County the expansion North Sumatra Province. The first model requires primary data while the second model requires data skunder time series starting in 2000 up to 2013. data analysis using two models, namely Structural Equation Models (SEM) and Vector Autoregression (VAR). Results of the study and this analysis gives an overview and prove the real poverty mapping in areas of expansion, poverty reduction actions based on the poverty mapping, control variables are very urgent in affects poverty, and controlling poverty continuously.